Implementasi Model PEMIKAT dalam Meningkatkan Aktivitas, Berpikir Kritis, Kerjasama, dan Hasil Belajar Pendidikan Pancasila Siswa - Nurul Amira; Aslamiah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Low levels of student learning activity, critical thinking skills, collaborative skills, and learning outcomes constitute issues that need to be addressed through the implementation of innovative learning models. One viable alternative is the PEMIKAT model, which integrates Problem-Based Learning and the "Make a Match" technique. This study aims to describe teacher activity and analyze student activity, critical thinking skills, collaborative skills, and learning outcomes. The study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, comprising the stages of planning, action implementation, observation, and reflection. It was conducted over four sessions with 12 third-grade students at SDN Benua Anyar 3, Banjarmasin. Data were collected through observation, tests, and documentation, and subsequently analyzed using qualitative and quantitative descriptive techniques. The results indicate that teacher activity met the "excellent" criterion; student activity reached the category where nearly all students were highly active; critical thinking and collaborative skills reached the category where nearly all students were proficient; and learning outcomes across the cognitive, affective, and psychomotor domains achieved classical mastery. Thus, the implementation of the PEMIKAT model effectively enhances the quality of Pancasila Education instruction by fostering active, collaborative, meaningful, and student-centered learning.